First Principles Studies on One-Photon and Two-Photon Absorption Properties of Symmetric Thiophene Derivatives - Li, Chungang; Wang, Zhihong (Asian Journal of Chemistry, 2014)
In this paper, the equilibrium geometries, one-photon, two-photon absorption properties and the transition nature of three thiophene derivatives have been theoretically studied by applying density functional response theory. Our calculated results have confirmed that the one-photon and two-photon absorption are enhanced and bathochromically shift with the increase of the strength of the D end-groups as well as the length of the conjugated system. The nonlinear optical phenomenons of the derivatives under investigation, originating from the intramolecular charge transfer within the p-conjugated system.